2007
DOI: 10.5694/j.1326-5377.2007.tb01171.x
|View full text |Cite
|
Sign up to set email alerts
|

Overweight, obesity and metabolic syndrome in rural southeastern Australia

Abstract: Objective: To measure the prevalence of overweight, obesity and the metabolic syndrome (MetS) in rural Australia. Design, setting and participants: Cross‐sectional surveys were conducted in two rural areas in Victoria and South Australia in 2004–2005. A stratified random sample of men and women aged 25–74 years was selected from the electoral roll. Data were collected by a self‐administered questionnaire, physical measurements and laboratory tests. Main outcome measures: Prevalence of overweight and obesity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 16 publications
3
53
2
Order By: Relevance
“…Details of the methodology of both studies have been published elsewhere 7–11. Discussed below is a brief summary of the setting, population and sample.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the methodology of both studies have been published elsewhere 7–11. Discussed below is a brief summary of the setting, population and sample.…”
Section: Methodsmentioning
confidence: 99%
“…Overall there were a total of 1563 participants, with a participation rate of 49%. A comparison of the socioeconomic background with population statistics available indicated that the participants were representative of the survey area populations [14]. …”
Section: Methodsmentioning
confidence: 99%
“…Such a broadening of perspective among genetic counselors and trainees may have downstream beneficial outcomes. For example, because psychological distress is significantly associated with a variety of negative health outcomes (Janus et al, 2007), enhancing deaf individuals’ psychological well-being could play a role in reducing health disparities in physical and mental health experienced by the deaf community (Barnett et al, 2011; Fellinger et al, 2012). …”
Section: Discussionmentioning
confidence: 99%